Determination of the impact location and damage characterization based on guided waves - De,Luca A; Sharif-Khodaei,Z; Caputo,F (2016)
The aim of this paper is to understand the effects of the damage criteria modelling on the training phase (performed by means of Finite Element simulations) of an artificial neural network (ANN) enabled to locate impacts onto a CFRP laminate. The developed FE models have been also used to investigate the intra-laminar damage mode, which, among different ones, has the most effects on the residual strength of the panel.